Earth orbital rhythms links timing of Deccan Trap volcanism phases and global climate change - Thomas Westerhold (PANGAEA, 2025)
In this study we combined in the data set published and new geochemical data generated on sediment cores drilled on the western Equatorial Pacific Shatsky Rise during DSDP Leg 86 (Site 577) and ODP Leg 198 (Sites 1209, 1210), drilled on the eastern South Atlantic Walvis Ridge by DSDP Leg 74 (Sites 525, 527, 528) and ODP Leg 208 (Sites 1262, 1267). To correlate the data in depth and time the records were initially studied regionally and then globally utilizing new high-resolution geochemical data, in particular high-resolution X-ray fluorescence (XRF) core scanning and bulk stable carbon isotope data. Non-destructive X-ray fluorescence (XRF) core scanning was used to perform testing of composite records, integrating data from multiple holes and sites by high resolution correlation and cyclostratigraphic or astronomical age model development. To combine Walvis Ridge sites we used published data from ODP Sites 1262 and 1267, but also generated new XRF data for cores from DSDP 525A-39R to 45R, DSDP 527*-30R to 34R, DSDP 528*-28R to 36R, ODP 1262-C14H, and ODP 1267B-36X at XRF Core Scanner III (AVAATECH Serial No. 12) at MARUM - Center for Marine Environmental Sciences - University of Bremen. For DSDP Site 577 as well as ODP Sites 1209 and 1210 XRF data were collected using XRF core scanner Avaatech serial no. 17 from the XRF core scanning facility located in at the IODP Gulf Coast Repository at Texas A&M University (College Station, USA). New benthic foraminifer carbonate δ13C and δ18O were measured on 404 samples at MARUM - Center for Marine Environmental Sciences - University of Bremen on Finnigan MAT 252 with Kiel III or ThermoFisher Scientific 253plus with Kiel IV automated carbonate preparation line. Abundances and isotopic compositions of Os were analyzed by negative thermal ionization mass spectrometry (Thermo Fisher Scientific TRITON) at Japan Agency for Marine-Earth Science and Technology (JAMSTEC), and abundances of Re were measured by an inductively coupled plasma-quadrupole mass spectrometer (Thermo Fisher Scientific iCAP-Q) at JAMSTEC.